Computer evaluation of VirE2 protein complexes for ssDNA transfer ability. (June 2017) - Volokhina, Irina; Gusev, Yury; Mazilov, Svyatoslav; Moiseeva, Yelizaveta; Chumakov, Mikhail
Graphical abstract: Highlights: The conformational properties of the pores inside the two and four-subunit VirE2 complexes have been explored by the molecular dynamics and normal modes methods. The possible functioning mechanism of the two and four-subunit VirE2 pore complexes has been predicted. Predicted complexes remain stable and do not decompose. Abstract: The single-stranded transfer DNA from the Ti plasmid of the soil bacteria Agrobacterium nonspecifically integrates into the plant chromosome and is inherited at subsequent cell divisions. How it is transferred across host membranes is unknown, but it is believed that VirE2 proteins form a membrane-spanning pore or channel in a lipid bilayer and possibly mediate the delivery of the single-stranded transfer DNA–VirD2–VirE2 complex to the plant cell chromosomes. The aim of this work was to perform a computer simulation of VirE2′s pore-forming capacity and an evaluation of constructed VirE2 complexes. The oscillating motions of complexes consisting of two and four VirE2 subunits were estimated by the molecular dynamics and normal modes methods. We did not predict any large changes in domain orientation for two and four-subunit VirE2 complexes within simulation times of 1 ns. A possible gating mechanism similar to that seen in the ion channels of the complex formed from two VirE2 proteins was proposed, whereas no conformational changes were predicted inside the pore in the complex formed from four VirE2 proteins.